Downstream: a natural history of the river - Bardach, John
Aerial view of a retreating mountain glacier. Water flow over a stone in a mountain stream. Typical midge larva. Stonefly Nymph. Larva of a net-winged midge. The origin of springs and wells. Ground water seepage in and out of a stream. Scud or sideswimmer. Water mite. A typical copepod. Rotifer. Aerial photograph of meanders and oxbows. Braided stream pattern in Alaska. Rwo mayfly nymphs. Ten typical stream animals on and under a stone. Caddisfly larva out of its shell. Case of the Caddisfly.